Meninjau Peluang Peningkatan Kompetensi Guru Penyandang Disabilitas Netra Sebagai Peserta Pelatihan Di Lingkungan Kementerian Agama RI - Restendi, Dedi; Nugraha, Firman; Ayundhari, Vidia Lantari (Fakultas Agama Islam Universitas Muhammadiyah Bandung, 2024)
This study aims to provide an overview of training programs for visually impaired teachers within the Ministry of Religious Affairs' office in West Java Province. The researchers employ a descriptive analysis method. Data collection is conducted through a regulatory study by reviewing official government websites related to the subject matter. Additionally, the researchers carry out a document analysis of training facilities and infrastructure and conducts field observations.The findings indicate that 1) there are no specific regulations that provide guidelines, instructions, or directives regarding the implementation of training programs for civil servants with visual impairments; 2) The inclusive education training curriculum can be utilized to accommodate visually impaired teacher; 3) The existing training facilities at the religious training center are not yet accessible for individuals with disabilities. Based on these findings, it can be concluded that visually impaired teachers have the same opportunities as their sighted counterparts to enhance their competencies in fulfilling their professional duties. Stakeholders should ensure that training facilities and infrastructure are accessible to visually impaired teachers.